Offentligt ansvarsutkrävande av vårdpersonal inom hälso- och sjukvården - Schager Wrisemo,Truls (2026)
This essay examines the conditions of the duties of healthcare professionals and the corresponding processes of accountability activated by negligent mistakes within the profession. Accountability is important in such a hazardous yet crucial societal institution as the healthcare system, where health workers is the primary insurance for a patient-safe healthcare. The risks threatening patient-safety can be of different types such as faults in the safety routines, technical malfunctions or stemming from the healthcare workers themselves, who sometimes commit humane or careless errors. The purpose of this essay is to examine the process of account-ability in situations where healthcare workers has committed negligent mistakes, and also why this process is stipulated the way it is. The research identifies two main parts of the process, one sort of accountability stemming from the public law domain which can mound to the Health and Social Care Inspectorate (IVO) directing critique alternatively the Medical Responsibility Board (HSAN) taking protective actions towards the license of the health worker. The other is the criminal responsibility obligated through the crimes negligently causing another’s death or personal injury or sickness. For the assessment of the violations within both these legal frameworks there is a standard of conduct which can be derived from the conditions of the healthcare workers’ professional duties, which are mainly defined through the public law domain but also dependent on several situational circumstances. The interests which motivate the process of accountability is adequate healthcare quality, patient-safety, society’s trust in the healthcare system, protection of life and health, as well as satisfaction of the patient’s needs. The work shows that the public law domain is more adapted to the specific context of healthcare than the punitive system since the assessment can be based on several more kinds of risks to a larger extent which can produce a more honest description of the unfortunate chain of events. This system however shows some serious concerns regarding lacking impartiality within the process which could jeopardize the satisfaction of the patient’s needs. The criminal responsibility has on the other hand flaws of more fundamental character since the process has negative effects on the patient-safety which it is said to protect and can furthermore be questioned from a moral point-of-view since the criminal behaviour in question is of relatively low reprehensible character. In order for the accountability process to be an effective part of the general pursuit of patient-safety it should be designed in a way which corresponds with the means and intentions of the regulation. The essay elaborates on the fundamental interests and motives of accountability, defining why the process looks the way it does, and lands in a conclusion that these interests must be implemented more effectively in the system in order to avoid accountability becoming an end of its own.
Keywords: Straffrätt; Förvaltnigsrätt; Medicinsk rätt; Hälso- och sjukvården; Ansvarsutkrävande processer; Vårdpersonalens yrkesansvar